Xylella fastidiosa subsp. pauca on olive in Salento (Southern Italy): infected trees have low in planta micronutrient content - SCORTICHINI, Marco; MIGONI, Danilo; ANGILÈ, Federica; DEL COCO, Laura; GIRELLI, Chiara Roberta; ZAMPELLA, Luigi; MASTROBUONI, Francesco; FANIZZI, Francesco Paolo (Phytopathologia Mediterranea, 2019)
Xylella fastidiosa subsp. pauca is associated with the olive quick decline syndrome in Salento (Apulia region, Southern Italy). The first outbreak of the disease was noticed in the Gallipoli district, from where it subsequently reached nearby areas. To date, no specific study has verified if abnormal soil or leaf micronutrients is associated with the disease. Soil and leaf samples were taken from 23 olive farms showing symptoms of the syndrome located in Gallipoli and nearby areas. Each sample was analyzed for magnesium and micronutrients content using inductively coupled plasma atomic emission spectroscopy. Real-time PCR indicated that X. f. subsp. pauca was present in each sampled tree. There is a general lack of molybdenum in soil and low bioavailability of copper and molybdenum in tree leaves. Low content of manganese in soil was also found in some farms located in Gallipoli, Galatone and Trepuzzi. Olive trees grown in Gallipoli area also had low content of boron. Principal component analysis showed that soil and leaf samples from this area had lower micronutrient contents compared with other areas. General copper depletion in leaves was uncommon and has not been previously recorded in Italy in a large area. This could indicate that X. f. subsp. pauca infection causes a depletion of copper within olive leaves. Reduced copper content has been previously recorded in leaves infected with X. f. subsp. multiplex and for other bacterial pathogens. The role of copper in relation to X. fastidiosa infection is discussed.